SURVEY AND SCIENTIFIC EVALUATION OF MEDICINAL PLANTS USED BY THE PAHAN AND TELI TRIBAL COMMUNITIES OF NATORE DISTRICT, BANGLADESH - Rahmatullah, Mohammed; Khatun, Zubaida; Hasan, Abid; Parvin, Waheda; Moniruzzaman, Md; Khatun, Asha; Mahal, Mostafi Jumrut; Bhuiyan, Md Shaiful Alam; Mou, Sadia Moin; Jahan, Rownak (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
The Pahans and the Telis are two of the smallest indigenous communities in Bangladesh. The Pahans, numbering about 14,000 people are widely scattered in several northern districts of the country, while the Telis are such a small community that nothing has been reported on their numbers and lifestyle. Both tribes are on the verge of disappearance. One each of the Pahan and the Teli community was located after much search in two adjoining villages of Natore district, Bangladesh. Since the tribes were found to still depend on their traditional medicinal practitioners for treatment of ailments, it was the objective of the present study to document their traditional usage of medicinal plants and to evaluate such plants against modern research-based pharmacological activity studies on these plants. Interviews were conducted of the practitioners of the Pahan and Teli community of Natore district with the help of a semi-structured questionnaire and using the guided field-walk method. Plant specimens as pointed out by the practitioners were collected and pressed on the field and identification completed at the Bangladesh National Herbarium. The Pahan tribal practitioners used 13 plants distributed into 9 families for treatment of 14 different ailments. The Teli tribal practitioner used 15 plants divided into 14 families for treatment of 17 different ailments. Eight out of the thirteen plants used by the Pahan tribal practitioner (61.5%) had reported relevant pharmacological activities in the scientific literature, while six out of the fifteen plants used by the Teli tribal practitioners (40%) had such relevant pharmacological activities in accordance with their usage. The medicinal plants used by the Pahans and Telis warrant further scientific studies toward discovery of lead compounds and efficacious drugs and the documentation and protection of the traditional medical knowledge held by these tribes.